2018
DOI: 10.1055/a-0608-4552
|View full text |Cite
|
Sign up to set email alerts
|

Static Postural Stability in Chronic Ankle Instability, an Ankle Sprain and Healthy Ankles

Abstract: To identify the single leg balance (SLB) test that discriminates among healthy, coper, and chronic ankle instability (CAI) groups and to determine effects of ankle muscles on the balance error scoring system (BESS) among the three populations. 60 subjects (20 per group) performed the SLB test with eyes open (EO) and eyes closed (EC). Normalized mean amplitude (NMA) of the tibia anterior (TA), fibularis longus (FL), and medial gastrocnemius (MG) muscles and BESS were measured while performing the SLB test. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…124,367 A systematic review by Rosen et al 376 found deficits in static and dynamic postural control in those with CAI. Similar findings were noted by other studies not included in the review by Rosen et al 22,89,105,116,138,167,205,239,250,258,260,352,376,392,405,485…”
Section: IIIsupporting
confidence: 89%
“…124,367 A systematic review by Rosen et al 376 found deficits in static and dynamic postural control in those with CAI. Similar findings were noted by other studies not included in the review by Rosen et al 22,89,105,116,138,167,205,239,250,258,260,352,376,392,405,485…”
Section: IIIsupporting
confidence: 89%
“…Similar to our results, one study showed lower MG EMG activity in individuals with CAI during single-leg stance when compared with healthy controls [ 31 ]. In contrast, one study reported greater MG EMG activity in the CAI group compared to the copers and healthy group [ 18 ]. In their study, Kwon et al reported that, during a single-leg balance test with eyes closed, the CAI group had higher fibularis longus and MG activity than the healthy and coper groups [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one study reported greater MG EMG activity in the CAI group compared to the copers and healthy group [ 18 ]. In their study, Kwon et al reported that, during a single-leg balance test with eyes closed, the CAI group had higher fibularis longus and MG activity than the healthy and coper groups [ 18 ]. Difference in testing protocols can be designated as the source of this discrepancy, with the Kwon study conducting balance tests in participants with their eyes closed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations